Histological advantages of two-component fibrin mesh (TachoSil) compared with polypropylene mesh after placementin the inguinal region in laboratory rats: Histološke prednosti dvo-komponentne fibrinske mreže (TachoSil) v primerjavi s polipropilensko mrežo po vstavitvipod mišični sloj in nad transverzalno fascijo v podganah - Arslani, Nuhi (Acta Medico-Biotechnica, 2025)
Hernia repair surgeries are among the most common procedures in both veterinary and human medi-cine, with various mesh options available for surgeons repairing the transversalis fascia. This study compared a variant of two-component fibrin mesh (TachoSil) and polypropylene mesh in reconstruct-ing the transversalis fascia by placing them in the inguinal region in Fischer laboratory rats. Specifically, the TachoSil or fibrin mesh was implanted into the groin region of Fischer rats, and after 30 days of mesh placement, the rats were sacrificed, the fibrous plate with either inserted mesh removed, and the tissue sent for histological analysis. The results showed that, compared with the polypropylene mesh, the implanted TachoSil mesh resulted in fewer postoperative complications and lower inflammatory cell presence.